(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2025)
This research looks at the creative HRM (human resource management) techniques used for training and development in Indore’s public and private banks. As India’s banking sector becomes more complicated due to globalization, privatization, and liberalization, HRM’s importance in guaranteeing organizational performance has increased. This study assesses procedures including written exams, job rotation, tailored training plans, and ongoing training needs assessment using data gathered from 320 workers at four banks. According to the report, public and private banks take different approaches to HRM strategies. The private sector places more of a focus on specialized project teams, customized training, and encouragement to utilize newly acquired abilities. These results highlight the need of strategic HRM strategies to maximize organizational development and personnel performance in a competitive setting.